Radio as an Agent for Social Change: A Study of Obonu FM - Owusu-Ofori, Frank (UniMAC-GIJ, 2015)
The study was undertaken to evaluate the role radio played in bringing social change in community development by accessing the effectiveness of Obonu FM. This was done by also assessing the general role of radio as an agent of social change. It was revealed that there is marginalisation of indigenous culture, norms and ideologies by the state-owned and, private media. There is also the sense that participation in the media and a sense of ownership in its operations are missing in the other forms of broadcasting. This calls for another force to whip up interest and participation in the media by the local people. The study also shows that Obonu FM is not really a community radio station technically speaking as station does not consult the members of the public before they develop their programmes. However, they give room for the people to participate through phone-ins, and through social media platforms that compensates for the initial inertia about public involvement.
Thesis